THU0451 Cause of death in patients diagnosed with giant cell arteritis in western norway 1972–2012 - Brekke, L.K.; Diamantopoulos, A.P.; Fevang, B.-T.; Assmus, J.; Gjesdal, C.G. (Annals of the rheumatic diseases, 2018)
BackgroundGiant cell arteritis (GCA) is the most common systemic vasculitis in adults.ObjectivesTo determine the causes of death in GCA patients during a 41 year period.MethodsHospital-based retrospective cohort study including patients diagnosed with GCA in Bergen Health Area during 1972–2012. Patients were identified through computerised hospital records using the International Classification of Diseases (ICD)-coding system. Clinical information was extracted from patients’ medical journals. We excluded patients if data were unavailable, if the reviewing rheumatologist found GCA to be an implausible diagnosis or if the American College of Rheumatology (ACR) 1990 classification criteria for GCA were not fulfilled. Information on cause of death was obtained from the Norwegian Cause of Death Registry (NCoDR). We grouped causes of death according to the European Shortlist for Causes of Death 2012-version (COD-SL-2012). Statistics Norway (www.ssb.no) provided background population data (all deaths during 1972–2012 in the Norwegian population ≥50 years of age). Statistical comparison was performed using mid-p values.ResultsThe patient inclusion process and patient characteristics have been published previously.1 A total of 792 patients were included, 566 (71.5%) females (mean age 73.5 years, SD 8) and 226 (28.5%) males (mean age 72.1, SD 9). 432 patients (54.5%) died during the study period (1 January 1972 – 31 December 2012). NCoDR had data on the cause of death for 431 of these. During the study period (1972–2012) there were 1635979 registered deaths in the general Norwegian population aged ≥50 years. The most frequent underlying causes of death in the overall study population were diseases of the circulatory system (53.4%), cancer (11.6%) and diseases of the respiratory system (10.0%). The most frequent causes of death in the general population were also diseases of the circulatory system (46.0%), cancer (22.8%) and diseases of the respiratory system (10.0%). The distribution of causes of death differed significantly between GCA-patients and the general Norwegian population (mid-p-value<0.001 both overall and stratified by sex). Absolute numbers of deaths and corresponding percentages of all causes of death stratified by sex are presented in figure 1.ConclusionsThe most frequent causes of death in our cohort of GCA-patients were diseases of the circulatory system, cancer and diseases of the respiratory system (including influenza and pneumonia). These were also the most frequent causes of death in the general Norwegian population aged ≥50 years, but the distribution of death causes differed significantly between GCA-patients and the general population. However, this might reflect differences in the composition of the populations that we were not able to adjust for. We aim to analyse this further by comparing our GCA-cohort with randomly selected age-, sex- and geographically matched control subjects.Reference[1] Brekke LK, Diamantopoulos AP, Fevang B-T, Assmus J, Esperø E, Gjesdal CG. Incidence of giant cell arteritis in Western Norway 1972–2012: a retrospective cohort study. Arthritis Research & Therapy2017;19:278. doi:10.1186/s13075-017-1479-6Disclosure of InterestL. Brekke Grant/research support from: MSD, A. Diamantopoulos: None declared, B.-T. Fevang Consultant for: Lilly, Novartis, AbbVie, J. Assmus: None declared, C. Gjesdal: None declared